Anthropological Approach to Islamic Education: Establishing Noble Spirituality in Overcoming Social Conflict - Firmansyah, Eka; Anwar, Saiful; Khozin, Khozin (Al-Hayat: Journal of Islamic Education, 2023)
This research examined how the anthropological approach to Islamic education is in building noble spirituality and overcoming problems of social conflict. The object of study is the student boarding school, Mahad Talhah bin Ubaidillah to be precise, Palu City, Central Sulawesi Province. This study uses a phenomenological approach, including a type of qualitative method. It collects data using observation interviews, documentation, and single data analysis (individual case analysis). The study's results found that the value of ukhuah Islamiyah was instilled to form students who always maintain unity and create harmonious relationships. Instilled noble moral values to shape students to become polite individuals, both in speech and in behaviour. In addition, it is customary to hold deliberations when facing problems, which is done to shape students into individuals who respect and respect the opinions of others, not feeling the most righteous themselves. As well as the habit of maintaining other people's privacy, this is to form students into individuals who do not like to interfere in private matters. Given that students live together in the dormitory. When these values are not instilled, they will disturb and damage the comfort of other students. This conclusion can become an idea for realizing good spirituality and can be a reference for overcoming social conflicts.